(untitled) (PIONIR: JURNAL PENDIDIKAN, 2021)
Transformational leadership is leadership that is able to create fundamental changes and is based on religious values, systems and culture to create innovation and creativity of its followers in order to achieve the vision that has been set. This research method uses a qualitative approach to library research. The data analysis technique uses content analysis. Related to this, transformational leadership can be seen as a process of influencing, at the micro level influencing between individuals and at the macro level an attempt to mobilize power to change social systems and improve institutions, especially madrasah/schools. At the macro-level analysis, transformational leadership performs activities such as expressing and mediating conflicts between groups. Conflicts between groups create organizational constraints, but at the same time can be useful for mobilizing followers towards organizational commitment.